2020
DOI: 10.3390/nu12051445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cod Residual Protein Supplementation on Markers of Glucose Regulation in Lean Adults: A Randomized Double-Blind Study

Abstract: Large quantities of protein-rich cod residuals, which are currently discarded, could be utilized for human consumption. Although fish fillet intake is related to beneficial health effects, little is known about the potential health effects of consuming cod residual protein powder. Fifty lean adults were randomized to consume capsules with 8.1 g/day of cod residual protein (Cod-RP) or placebo capsules (Control group) for eight weeks, in this randomized, double-blind study. The intervention was completed by 40 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A higher dose was evaluated by Vildmyren et al , 59 who carried out a randomised double-blind study aiming to investigate whether the ingestion of cod protein (8.1 g per day) for two months alters the levels of markers of glucose regulation in lean adults ( n = 50, mean age of 28 years old). The authors indicated that fasting glucose or insulin concentrations were not significantly different when the test item was ingested, but the levels of ketone bodies decreased in the subjects, together with an increase of trimethylamine N -oxide concentration in plasma and urine, which are parameters related to impaired glucose metabolism.…”
Section: Description Of Resultsmentioning
confidence: 99%
“…A higher dose was evaluated by Vildmyren et al , 59 who carried out a randomised double-blind study aiming to investigate whether the ingestion of cod protein (8.1 g per day) for two months alters the levels of markers of glucose regulation in lean adults ( n = 50, mean age of 28 years old). The authors indicated that fasting glucose or insulin concentrations were not significantly different when the test item was ingested, but the levels of ketone bodies decreased in the subjects, together with an increase of trimethylamine N -oxide concentration in plasma and urine, which are parameters related to impaired glucose metabolism.…”
Section: Description Of Resultsmentioning
confidence: 99%
“…The main difference between the two periods was an exchange of imported meat with marine sources, but total E% from protein was higher in the Traditional diet. Beneficial effects of isolated fish protein on glycemic control (52,53) and markers of IGT (54) have been reported in RCTs.…”
Section: Discussionmentioning
confidence: 99%